Anatomic Coracoclavicular Ligament Reconstruction for the Treatment of Acute Acromioclavicular Joint Dislocation - Daisuke Mori, MD; Fumiharu Yamashita, MD, PhD; Kazuha Kizaki, MD; Noboru Funakoshi, MD; Yasuyuki Mizuno, MD; Masahiko Kobayashi, MD, PhD (JBJS Open Access, 2017)
Background:. The long-term clinical and radiographic outcomes following coracoclavicular (CC) ligament reconstruction for the operative treatment of acute acromioclavicular (AC) joint dislocation remain uncertain. The purpose of the present study was to determine the long-term clinical and radiographic outcomes of CC ligament reconstruction and to identify risk factors for unfavorable outcomes. Methods:. We reviewed 20 cases of AC joint dislocation in 19 patients (18 male and 1 female; mean age, 32.3 years) that were treated with single-bundle reconstruction. The mean duration of follow-up was 12.7 years. We measured the CC vertical distance (CCD) on the anteroposterior view and compared the affected and unaffected sides (CCD ratio). We divided the patients into those with a CCD ratio of <25% (Group 1) and those with a CCD ratio of ≥25% (Group 2). We radiographically investigated the clavicular tunnel anteroposterior (CTAP) angle, clavicular tunnel ratio, and coracoid tunnel orientation on the basis of the entry and exit points at the base of the coracoid. For the coracoid tunnel orientation, we compared center-center orientation and noncenter-center orientation. Results:. Group 1 comprised 17 cases (85%), and Group 2 comprised 3 cases (15%). At the time of the latest follow-up, Group 1 had a significantly higher mean Constant score than Group 2 (98.2 compared with 90.7; p = 0.038). Of the 3 radiographic parameters, only the CTAP angle was significantly different between the 2 groups (p < 0.0001). Two (67%) of the 3 cases in Group 2 were associated with posterior AC joint displacement. Conclusions:. CC ligament reconstruction for the treatment of acute AC joint dislocation resulted in successful long-term clinical and radiographic outcomes. It is important to decrease the CTAP angle and to ensure proper anatomic placement of the clavicular and coracoid tunnels at the time of surgery. Level of Evidence:. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.